EFFECT OF TBT IN ACETYLCHOLINESTERASE OF PERNA PERNA (LINNAEUS, 1758) (MYTILIDAE) - Moes, Artur (2020)
Acetylcholinesterase (AChE) is one of the most well-known biomarkers in ecotoxicological monitoring programs of organophosphates and carbamates. However, some studies suggest that acetylcholinesterase also act as a biomarker for other xenobiotics. With this approach we conducted comparison tests of this biomarker in two locations in the city of Arraial do Cabo – RJ, Brazil. Dos Anjos Beach is a cove that has a port considered as an environment impacted by tributyltin, with the oceanic beach Praia Grande introduced in our study as a reference environment. In two samples (03/04/2004 and 09/06/2005) the specific activities of acetylcholinesterase activity in gills of Pernaperna were higher in Dos Anjos Beach corroborating laboratory experiments conducted by other authors. Additional studies are important for the determination of imposex associated with acetylcholinesterase, and can also integrate the function of biomarkers for exposure to tributyltin in molluscs.